2015
DOI: 10.1002/phar.1596
|View full text |Cite
|
Sign up to set email alerts
|

Agranulocytosis with Ceftaroline High‐Dose Monotherapy or Combination Therapy with Clindamycin

Abstract: Clinicians should have a heightened awareness of agranulocytosis when using ceftaroline in such settings and monitor complete blood counts at least once/week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 7 publications
(11 reference statements)
0
22
0
Order By: Relevance
“…Overall, ceftaroline salvage therapy in patients with MRSA bacteremia with or without IE demonstrated an overall success rate of approximately 80%. With vancomycin clinical failure rates reported up to 24% in MRSA bacteremia, ceftaroline is an attractive alternative [29]. Bone and joint infections are another major cause of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, ceftaroline salvage therapy in patients with MRSA bacteremia with or without IE demonstrated an overall success rate of approximately 80%. With vancomycin clinical failure rates reported up to 24% in MRSA bacteremia, ceftaroline is an attractive alternative [29]. Bone and joint infections are another major cause of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, agranulocytosis is listed as a postmarket adverse event on the FDA Medwatch [28]. Several recent safety studies have evaluated this and reported agranulocytosis complicating 13% of courses of ceftaroline treatment, which are summarized in Table 2 [29–32]. A few cases were severe with an absolute neutrophil count of 0 cells/mm [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adverse effects related to ceftaroline use are rarely described. Multiple observational and case report studies have suggested that ceftaroline exposure is associated with higher rates of neutropenia than seemingly listed in the product package insert . The prolonged use of ceftaroline in off‐label, difficult‐to‐treat clinical scenarios may potentiate the risk of neutropenia and contribute to additional patient morbidity and mortality, particularly if adequate follow‐up laboratory monitoring is not performed …”
mentioning
confidence: 99%
“…Prolonged durations of high‐dose ceftaroline (i.e., 600 mg 3times daily) are typically prescribed for serious infections such as endocarditis or osteomyelitis . Although neutropenia is a known adverse effect of β‐lactam antibiotics, the number of reports suggesting ceftaroline‐associated neutropenia is concerning . Whereas the causal relationship of this association remains unclear when comparing ceftaroline to other β‐lactams, the potential effects of non–chemotherapy‐associated neutropenia could lead to an increased propensity for severe infection, hospital readmission, prolonged hospitalization length of stay (LOS), increased cost, and increased patient mortality …”
mentioning
confidence: 99%